A game-theoretic approach to nuclear fuel cycle transition analysis under uncertainty. (March 2020) - Phathanapirom, U.B.; Haas, D.A.; Leibowicz, B.D.
Highlights: A fuel cycle transition scenario is cast as a sequential game against nature. Distinct character archetypes are depicted through unique importance criteria weights. Chosen fuel cycle schemes are sensitive to probability distributions over uncertain technoeconomic outcomes. Abstract: We present a novel methodology for optimizing nuclear fuel cycle transitions that incorporates a game-theoretic approach and captures interactions among multiple decision makers. The methodology is demonstrated using a two-person sequential game with uncertainty, where the two players represent a policy maker and an electric utility company, though the method generalizes to any number and type of individual decision making entities. Coupled with a sophisticated nuclear fuel cycle simulator, rich transition scenarios may be analyzed to identify robust transition strategies. These strategies explicitly treat uncertainties using a stochastic programming approach, devising optimal near-term hedging strategies that simultaneously consider all possible states of the world, maintaining flexibility to allow for intelligent recourse decisions once uncertainties are resolved. In the demonstration game, reactor technology and fuel cycle scheme adopted by the electric utility are shown to depend on both the policy maker's decisions and the distributions over uncertain technological and economic outcomes.